The Growth and Yield of Sweet Sorghum (Sorghum bicolor (L.) Moench) On The Mulch Treatments and Organic Matter - Novrizal Siregar; Teuku Irmansyah; Mariati Mariati (Jurnal Agroekoteknologi, 2016)
The research has been conducted to evaluation growth and yield of sweet sorghum on the mulch treatments and organic matter. The research was conducted at experimental field, Agricultural Faculty University of Sumatera Utara, Medan with altitude ± 25 meter above sea level, began from April up to August 2015. The experiment was arranged by split plot design with mulch as main plot (without mulch, hay mulch) and organic matter as sub plot i.e., without organic matter, empty fruit bunch compost,chicken manure and mixture of empty fruit bunch compost and chicken manure. Parameters observed were plant lenght, leaves number, stem diameter, flowering time, seed weight per sample, seed weight per plot and weight of 1000 seeds. The results showed that, among all parameters observed, only leaves number was significantly affected by mulch treatment. However there were variations of plant lenght, leaves number, and stem diameter on organic matter treatments. B3 treatments (mixture of empty fruit bunch compost and chicken manure) produced the highest plant length (296.88 cm), the highest leaves number (5.83 strands) and the largest stem diameter (5.38 mm).There was no interaction between mulch treatments and organic matter.